Immunophenotyping pattern of mixed phenotypic acute leukemia: historical review and diagnostic pitfalls - Monika Gupta; Pooja Dhamija; Nisha Marwah; Sujata Kumari SP Prasad; Rajeev Sen (Journal of Pathology of Nepal)
Introduction: Multiparametric approaches are used for the diagnosis and classification of acute leukemia. Even after extensive immunophenotyping, a rare and heterogeneous subgroup that cannot be readily classified as Mixed Phenotypic Acute leukemia in which the blasts exhibit the antigens of more than one lineage. This study aimed to analyze the incidence of Mixed Phenotypic Acute Leukemia and correlate the clinicopathological and immunophenotypic characteristics.